Integrating digital business strategies and accounting information systems to enhance profit growth: Evidence from culinary MSMEs - Muhammad Sahal Ridho; Sari Rahmadhani (Institute of Accounting Research and Novation (IARN), 2026)
The rapid development of digital technology has transformed the way micro, small, and medium enterprises (MSMEs) conduct their business activities, particularly in the culinary sector in Semarang City. However, the utilization of e-commerce, digital marketing, and accounting information system applications in business management has not been fully integrated, which may limit the ability of MSMEs to achieve optimal profit growth. This study examined the influence of e-commerce, digital marketing, and business scale on profit growth, while also investigating the mediating role of accounting information system applications. A quantitative approach was applied using survey data collected from 205 MSME owners through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling to evaluate both direct and indirect relationships among variables. The findings indicated that digital marketing and business scale had a positive and significant effect on profit growth, while e-commerce did not show a direct significant effect. In addition, accounting information system applications significantly influenced profit growth and mediated the relationship between e-commerce and business scale with profit growth. These results highlight the importance of integrating digital business strategies with accounting information systems to improve financial performance and support the sustainability of MSMEs.